2003
DOI: 10.1889/1.1832558
|View full text |Cite
|
Sign up to set email alerts
|

54.2: A High Dynamic Range Display Using Low and High Resolution Modulators

Abstract: We have developed an emissive high dynamic range (HDR) display that is capable of displaying a luminance range of 10,000cd/m2 to 0.1cd/m2 while maintaining all features found in conventional LCD displays such as resolution, refresh rate and image quality. We achieve that dynamic range by combining two display systems — a high resolution transmissive LCD and a low resolution, monochrome display composed of high brightness light emitting diodes (LED). This paper provides a description of the technology as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
100
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(100 citation statements)
references
References 1 publication
0
100
0
Order By: Relevance
“…In a second study, the same threshold (90% preference level) was been reported for three groups of participants with the following values: 4,677 cd/m 2 for technical, 3,090 cd/m 2 for arts and 1,995 cd/m 2 for naive participants [34]. Both experiments were conducted on a dual modulation HDR display system [35], with the ability to reproduce luminance levels in the range from 0.004 to 20,000 cd/m 2 . Seven images were evaluated, six of which were real-world structured stimuli, using 34 participants.…”
Section: Objective Evaluationmentioning
confidence: 69%
“…In a second study, the same threshold (90% preference level) was been reported for three groups of participants with the following values: 4,677 cd/m 2 for technical, 3,090 cd/m 2 for arts and 1,995 cd/m 2 for naive participants [34]. Both experiments were conducted on a dual modulation HDR display system [35], with the ability to reproduce luminance levels in the range from 0.004 to 20,000 cd/m 2 . Seven images were evaluated, six of which were real-world structured stimuli, using 34 participants.…”
Section: Objective Evaluationmentioning
confidence: 69%
“…Relative (and even absolute) luminances are maintained, and edges will be reproduced exactly when they are below the maximum contrast of the front display of about 250 : 1 in the current production model. Only when this range is exceeded is some fidelity lost near high contrast boundaries, but this effect is well below the detectable threshold, and has not been visible in any experiments [65].…”
Section: Local Contrast Perceptionmentioning
confidence: 89%
“…From the psychophysical theory presented in Section 2.1.1 we can establish the largest size of a rear image pixel. A second version [11,71] of the HDR display uses light emitting diodes (LED) at the largest possible size allowed by the veiling luminance effect that has been validated previously through experimental tests [65]. For a full white box occupying the center third of the screen, the maximum luminance 3 Display manufacturers often employ various methods of distorting the calculation of dynamic range, such as altering room illumination between measurements.…”
Section: Led-based Displaymentioning
confidence: 99%
See 1 more Smart Citation
“…The colour wheel was removed and the greyscale video was projected through an array of lenses onto the back of a 15" XGA colour Sharp LQ150X1DG0 LCD display. The system was capable of displaying HDR images with a dynamic range of more than 75,000 : 1 [34]. els.…”
Section: Displaysmentioning
confidence: 99%